Learning Islamic Religious Education Through the Islamic Character Program at SMP IT Hikmatul Ulum - Wildan Mahmudin; Nadia Kurnia Fauzia; Mada Sumringah Sari; Uus Ruswandi; Bambang Samsul Arifin (al-Afkar, Journal For Islamic Studies, 2025)
The purpose of education is the dominant aspect of education. Therefore, discussing Islamic Religious Education, both its meaning and objectives, must refer to the instilling of Islamic values (cultivating a sense of religion) and must not neglect social ethics or morality. Instilling these values also aims to foster success in life for students in this world, which will then be able to produce goodness in the afterlife. This research is field research, namely research conducted directly in the field or with respondents. The purpose of field research is to examine the issues raised in the research by conducting a review of the problem in real-life conditions. The results of the research conducted at SMP IT Hikmatul Ulum are that the instillation of Islamic character is instilled in the form of habits of praying at the beginning of prayer times, reading the Quran, memorizing short surahs, and saying greetings. Although in practice many students still have shortcomings in deepening these principles, educators strive to instill Islamic character in accordance with the guidance and guidelines of the implemented curriculum.